The Effects of Solvents and Extraction Methods on the Antioxidant Activity of P. niruri (Jurnal Teknologi (Sciences & Engineering), 2014)
The effects of different types of solvents and extraction method were investigated to determine the presence of antioxidant contents and activity from the P. niruri plant. The aim of this study is to determine which extraction method will give higher natural antioxidant contents and antioxidant activity. The content of natural antioxidant and antioxidant activity were analysed by total phenolic content (TPC), total flavonoid content (TFC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay. The results showed that extracts from a supercritical fluid extraction (SFE) method without the addition of modifier showed the highest content of total phenolic (187.66 mg GAE/ g) and flavonoid (1100.93 mg QE/g) in P. niruri compared to the other methods of extraction with different type of solvents. The extract of P. niruri from different extraction methods showed antioxidant activity on DPPH radical scavenging assay. The soxhlet extraction method by methanol showed the lowest IC50 compared to the other methods of extraction. The results revealed that P. niruri extracts had different content of antioxidant and antioxidant activity. The solvent polarity and different methods of extraction play significant roles in determining the most suitable method for production of antioxidant contents and antioxidant activity from P. niruri extracts.